Young Muslim women on the face veil (niqab): A tool of resistance in Europe but rejected in the United States - Shirazi, Faegheh; Mishra, Smeeta (International Journal of Cultural Studies, 2010)
In order to understand Muslim women’s views on veiling in the West, one must take into account historical and socio-political factors such as a country’s colonial/national history, the nature of its immigration regime, the demographic composition of immigrant groups, and how the nation operationalizes concepts such as secularism and citizenship. While academic literature and media reports on young Muslim women in Europe indicate that wearing the niqab or face veil is often viewed as an act of rebellion or a form of personal/political/religious identity, our in-depth interviews of young Muslim women in the United States reveal a different story. While half the participants in this study wore a headscarf or hijab, not one of them said they were interested in wearing the niqab. Instead, they believed the niqab was unnecessary in the American context. However, an overwhelming majority upheld the right of a woman to wear a niqab if she wanted to do so. Two American Muslim women narrated why they gave up wearing the niqab after wearing it for a short time.
Keywords: approches et analyses; cours; discipline; féminisme islamique; point de vue situé; premier cycle; ressource en ligne; sex2283